Chemical composition and antimicrobial activity of essential oil from Pyrethrum pulchrum Ledeb. - Erdenetsogt, Uugangerel; Gotov, Choijamts; Voigt, Kerstin; Bartram, Stefan; Boland, Wilhelm; Dagvadorj, Enkhmaa (Mongolian Journal of Chemistry, 2018)
The chemical composition and antimicrobial activity of the essential oil from the aerial parts of Pyrethrum pulchrum Ledeb. were investigated. Dried plant material was hydro-distillated yielding 0.1% of essential oil. The oil was analyzed by GC-MS techniques. Fifty-five compounds were identified representing 99.7% of the total oil composition. Camphor was the predominant compound (33.9%) followed by linalool (21.1%) and α-pinene (9.0%). The antimicrobial activity of the oil was determined using the disk diffusion method against Gram-positive bacteria (Bacillus subtilis, Staphylococcus aureus and Enterococcus faecalis), Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli), Mycobacterium vaccae and fungi (Candida albicans, Sporidiobolus salmonicolor and Penicillum notatum). The essential oil of P. pulchrum displays an intermediate activity against selected bacteria.